FORMATIVE EVALUATION CHALLENGES OF MATHEMATICS FROM THE UNIVERSITY VIRTUAL CLASSROOM - Bilbao Consuegra, Maida L.; Nieto Almeida, Lázaro E. (Atenas, 2014)
The teaching-learning process constitutes a central axe in the improvement and change that takes place in Senior Education in Cuba. All components of the educational process are to receive special attention in the current research directions, it has been demonstrated that there is a marked imbalance in this respect, identifying learning evaluation as one of the least developed components. The paper presents a didactic methodological conception for the learning evaluation of mathematics from the University virtual classroom as a solution to the needs concretized in the culminated research projects.